The importance of peer relatedness at school for affective well‐being in children: Between‐ and within‐person associations. Issue 4 (6th June 2019) - Schmidt, Andrea; Dirk, Judith; Schmiedek, Florian
Abstract: Two intensive longitudinal studies examining the association between children's feeling of relatedness to peers at school and their affective well‐being were performed. In Study 1, 110 third and fourth graders reported on their positive affect (PA) and negative affect (NA) 4 times daily and on their peer relatedness once a day over 4 weeks. Multilevel analyses revealed that children who reported higher peer relatedness on average also reported higher PA and lower NA (between‐person associations). Moreover, on days when children reported higher peer relatedness than usual, they also reported higher PA, but they did not necessarily report lower NA (within‐person associations). In Study 2, 55 fourth, fifth, and sixth graders indicated their PA, NA, and peer relatedness once a day over 2 weeks. We replicated the findings of Study 1 on both levels. The studies showed that feeling related to peers is associated with high PA at school and at home on a daily basis, illustrating the function of peer relatedness in promoting positive well‐being. The findings further demonstrated the necessity of intensive longitudinal studies focusing on within‐person associations and the importance of measuring both PA and NA in order to capture effects on affective well‐being thoroughly.